2016
DOI: 10.1021/acs.energyfuels.6b02035
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Speciation and Distribution in an Egyptian Natural Gas Processing Plant

Abstract: Unprocessed petroleum hydrocarbons often contain high concentrations of mercury (Hg), which can severely damage the metal components of a processing plant and pose a health risk to the workers and the natural environment. Although Hg removal units can significantly reduce the Hg concentration in the export products, they are often installed in the final stage of the processing plant, thus failing to protect the production facilities. In this study, Hg distribution within a natural gas processing plant was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…To the authors' knowledge, biomethane has only been in situ sampled directly on the pipelines at the grid pressure (40 bar a ) by Cachia et al 22 using a high-pressure acid bubbling impinger for the direct preconcentration of metallic TC in gas samples. 31 So far, other reported determinations of TC in high-pressure gases (typically natural gas) have always been carried out by depressurization of the gas and preconcentration at atmospheric pressure: the gas is either depressurized in situ from the pipe aer what the sampling system is installed at atmospheric pressure, 32 or it is sampled at its grid pressure in surface-treated high-pressure stainless-steel cylinders subsequently transported to the lab for depressurization and preconcentration. 29,[33][34][35][36] Depressurization is detrimental to the preconcentration of TC since, assuming the ideal gas law PV ¼ nRT, a dilution factor equal to the ratio of the high pressure to the pressure aer depressurization leads to a concentration decrease of the TC, implying larger gas volumes have to sampled at atmospheric pressure than at high pressure to trap a given amount of TC.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, biomethane has only been in situ sampled directly on the pipelines at the grid pressure (40 bar a ) by Cachia et al 22 using a high-pressure acid bubbling impinger for the direct preconcentration of metallic TC in gas samples. 31 So far, other reported determinations of TC in high-pressure gases (typically natural gas) have always been carried out by depressurization of the gas and preconcentration at atmospheric pressure: the gas is either depressurized in situ from the pipe aer what the sampling system is installed at atmospheric pressure, 32 or it is sampled at its grid pressure in surface-treated high-pressure stainless-steel cylinders subsequently transported to the lab for depressurization and preconcentration. 29,[33][34][35][36] Depressurization is detrimental to the preconcentration of TC since, assuming the ideal gas law PV ¼ nRT, a dilution factor equal to the ratio of the high pressure to the pressure aer depressurization leads to a concentration decrease of the TC, implying larger gas volumes have to sampled at atmospheric pressure than at high pressure to trap a given amount of TC.…”
Section: Introductionmentioning
confidence: 99%
“…These specifications ensure high quality gas for combustion but are also essential to prevent damage to facilities and protect consumer health. However, studies have revealed the presence of arsenic compounds, mercury and other metals/metalloids in natural gas from different origins at very low concentrations ranging from 10 −1 to 10 3 µg/m 3 [6][7][8][9][10][11]. These elements have well-known risks and potentially can cause industrial damage, such as through corrosion or catalytic poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, mercury speciation studies in gas condensates have mainly been focused on elemental, organic and inorganic mercury, mainly relying on separation by Gas or Liquid Chromatography and detection by ICP-MS 9 . The particulate Hg is then calculated as the difference between total Hg and the sum of all the other species.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there is a need to identify exactly which species of mercury are present. The total amount of Hg should fulfill the following mass balance equation To the best of our knowledge, mercury speciation studies in gas condensates have mainly been focused on elemental, organic, and inorganic mercury, mainly relying on separation by gas or liquid chromatography and detection by inductively coupled plasma-mass spectrometry (ICP-MS) . The particulate Hg is then calculated as the difference between total Hg and the sum of all of the other species.…”
mentioning
confidence: 99%
See 1 more Smart Citation